Full employment has not been achieved: Full employment policy ; theory and practice - Dimitri B. Papadimitriou (Levy Economics Institute of Bard College, 1999)
Claims that the nation has reached full employment take for granted the need for a reserve pool of labor to maintain price stability and labor market flexibility. But are millions of jobless and underemployed workers the best we can do in these times of economic expansion? And what will happen when the inevitable downturn comes? Reduction of the workweek and employment subsidies have been proposed to achieve higher employment, but neither is sure to raise employment and both may have serious side effects. A public service employment program that offers jobs at a fixed wage to all who are willing and able to work can provide full employment without inflationary pressures and with labor market flexibility, preserve workers' skills, contribute valuable public services, and be relatively inexpensive.
Keywords: 330